Hysterectomy as forced sterilization in intellectual disabilities Adolescences: legal and Ethical Argumentations - Alshdefat, Aisha; Baker , Rasha Abu; Francis, Frincy (International Journal of Psychosocial Rehabilitation, 2020)
Hysterectomy as a forced sterilization method for intellectual disabilities(ID) women for a long time led to designed laws to protect women with intellectual disabilities, and keep their rights. Individuals should not refuse sterilization merely because they may also be vulnerable to violence. Recently, there are medical and surgical options available to manage menstrual of adolescents with intellectual disabilities (ID). Ethically, opponents considered forced sterilization as violence against women and against their right. Whereas proponents believed forced sterilization as morally justified and that parents have the right to manage the menstrual problem in their kids who is with intellectual retardation. Mentally disabled women's sterilization is an ethical dilemma that needs toaddressed in health care. Sterilization has made a huge legal, moral, and religious controversy on many levels. The current author is against forced sterilization to preserve human rights and dignity of women with intellectual disabilities. The author position this Dilma" Hysterectomy in intellectual disabilities Adolescence: legal and Ethical Argumentations" Therefore, the overall aims of this paper to present arguments on forced sterilization for women with intellectual disabilities from the opponents and proponents' legal and ethical views.